Designing Student Worksheets (LKM) Based on the Rigorous Teaching and Learning (RTL) Model - Ade Mirza; Revi Lestari Pasaribu; Justin Eduardo Simarmata (Pendidikan Matematika UNIMOR, 2024)
This research aims to design Student Worksheets (LKM) for the Discrete Mathematics course, where the LKM design is structured so that the LKM can be used in the Rigorous Teaching and Learning (RTL) learning model. The results of the lecturers' reflections found that the main problem lies in the content of the material in textbooks which is not interesting, students are often unable to understand the textbooks they own, especially in solving the questions given. This has implications for 1) lack of motivation to learn, 2) lack of understanding of the material, 3) fear of expressing opinions, and 4) lectures are less effective and less enjoyable. Therefore, teaching materials need to be packaged appropriately according to the substance and conditions of students in LKM. The research design used in this research is Thiagarajan's 4-D development model. This model is a system of educational development approaches that are carried out in 4 sessions, namely Define or Introduction where in this session preliminary analysis, student analysis, and needs analysis are carried out, Design or Planning where in this session what is done is format selection, initial design and design preparation, Develop or Development where in this session validation and limited trials are carried out, as well as Disseminate or Disseminate where in this session the LKM is given to the teaching lecturers. This research produces an LKM that is used in Discrete Mathematics courses.